1984
DOI: 10.1007/bf00427772
|View full text |Cite
|
Sign up to set email alerts
|

Serum neuroleptic concentrations and clinical response: A radioreceptor assay investigation of acutely psychotic patients

Abstract: Twenty-two acutely psychotic patients were rigorously assessed for psychopathology at baseline and after 14 days of neuroleptic treatment. The neuroleptic radioreceptor assay (NRRA) was used to determine serum neuroleptic concentrations. Serum neuroleptic concentration was significantly, nonlinearly related to changes in BPRS Total Score, and BPRS Factor Scores for Thought Disturbance and Anxiety-Depression. Clinical improvement was associated with intermediate (11-50, 51-126 ng/ml haloperidol equivalents) whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…From their first study, Tune et al (1980) reported a significant correlation between clinical state and neuroleptic serum levels in 30 schizophrenic patients receiving various neuroleptic drugs. The same researchers later reported, from a study including 22 acutely psychotic patients who had been treated for 2 weeks with various neuroleptic drugs, a possible 'therapeutic window' between II and 126 IJ.gJL haloperidol equivalents (Kucharski et al 1984).…”
Section: Neuroleptic Plasma Concentrations By Rra 43mentioning
confidence: 94%
“…From their first study, Tune et al (1980) reported a significant correlation between clinical state and neuroleptic serum levels in 30 schizophrenic patients receiving various neuroleptic drugs. The same researchers later reported, from a study including 22 acutely psychotic patients who had been treated for 2 weeks with various neuroleptic drugs, a possible 'therapeutic window' between II and 126 IJ.gJL haloperidol equivalents (Kucharski et al 1984).…”
Section: Neuroleptic Plasma Concentrations By Rra 43mentioning
confidence: 94%
“…In other words, there is a “therapeutic window” for dose or plasma levels [25,44,64,112,125]. This concept has been discussed in earlier publications by the present author [86,87].…”
Section: Definition In Practice Of Individual Sensitivity To Antipsycmentioning
confidence: 98%
“…high-dose HPL in treatment resistant cases must be weighed against the small but notable numbers of sudden deaths on high dose HPL (Flaherty and Lahmeyer, 1978;Ketai, Matthews and Mozdzen, 1979;Modestin, Krapf and Boker, 1981). It has been suggested that serum HPL estimations would be valuable in optimizing the use of this drug (Mendlewicz et al, 1981;Maglozzi et al, 1981;Smith et al, 1982;Mavroidis et al, 1983;Extein, Pottash and Gold, 1983;Kucharski et al, 1984;and Potkin et al, 1985) particularly in 'treatment-resistant' patients (Hollister and Kim, 1982). Our results suggest, however, that there is no advantage in exceeding serum levels of 5-20 ng/ml, and that this therapeutic range is generally achieved with daily doses of 10-40 mg, but that a 'therapeutic window' effect is not usually observed in chronic schizophrenic patients.…”
Section: Discussionmentioning
confidence: 96%
“…High dose HPL treatment does not appear to offer advantages to the majority of acutely ill schizophrenic patients (Ericksen, Hurt and Chang, 1978;Donlon et al, 1980;Modestin et al, 1983) and may cause i unacceptably high levels of unwanted side-effects (Bollini et al, 1984). A curvilinear relationship has been suggested by several authors and a range of 'therapeutic windows' proposed: [8][9][10][11][12][13][14][15][16][17][18] ng/ml (Magliozzi et al, 1981) 5-15 ng/ml (Smith et al, 1982;Extein, Pottash and Gold, 1983) 4.2-11.0 n /ml (Mavroidis et al, 1983) 11-126 ng ml (Kucharski et al, 1984) 4-26 ng/ml (Potkin et al, 1985) 6.5-16.5 ng/ml (Smith et al, 1985) Hollister and Kim (1982) proposed a therapeutic range at a higher level (20-50 ng/ml) for 'treatment-resistant' cases.…”
Section: Introductionmentioning
confidence: 98%